Chaos Theory and Organization - Thiétart, R. A.; Forgues, B. (Organization Science, 1995)
Many authors have stressed the existence of continuous processes of convergence and divergence, stability and instability, evolution and revolution in every organization. This article argues that these processes are embedded in organizational characteristics and in the way organizations are managed. Organizations are presented as nonlinear dynamic systems subject to forces of stability and forces of instability which push them toward chaos. When in a chaotic domain, organizations are likely to exhibit the qualitative properties of chaotic systems. Several of these properties—sensitivity to initial conditions, discreteness of change, attraction to specific configurations, structural invariance at different scales and irreversibility—are used to establish six propositions. First, because of the coupling of counteracting forces, organizations are potentially chaotic. Second, the path from organizational stability to chaos follows a discrete process of change. Third, when the organization is in the chaotic domain, small changes can have big consequences that cannot be predicted in the long term. Fourth, from chaos, new stabilities emerge—the strange attractors—which are assimilated to organizational configurations. Fifth, similar patterns should be found at different scales. Finally, during one single organizational life span or between two different organizations similar actions should never lead to the same result.